Double Total Domination in Harary Graphs - Kazemi, Adel P.; Pahlavsay, Behnaz (Communications in Mathematics and Applications, 2017)
Let \(G\) be a graph with minimum degree at least 2. A set \(D\subseteq V\) is a double total dominating set of \(G\) if each vertex is adjacent to at least two vertices in \(D\). The double total domination number \(γ _{× 2,t}(G)\) of \(G\) is the minimum cardinality of a double total dominating set of \(G\). In this paper, we will find double total domination number of Harary graphs.